Grey-Smith Institute for Creative Arts - Pendal, Simon; Neille, S. (2015)
For those who inhabit places of learning: discover the inventive and artful in the use of brick and block masonry. For the general reader: this collection is a snapshot of Australian design that deserves recognition.